Students’ perceptions and learning approaches in accounting: the role of mobile apps technology / Marziana Madah Marzuki … [et al.] - Marzuki, Marziana Madah; Nik Abdul Majid, Wan Zurina; Salwani, Roslina; Mohd Zawawi, Mohd Zafian; Abu Bakar, Hatinah (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
The objective of this paper is first to investigate students’ perception on the accounting subject and how the perceptions influence their approaches in learning. In addition, this study investigates students’ perceptions on the role of mobile-app technology in their approaches of accounting learning. Based on the self-administered structured questionnaire developed and distributed to 153 respondents that comprised of non-accountings students from all branches of Universiti Teknologi MARA (UiTM) in Malaysia, the results find that there is significant relationship between students’ perceptions on accounting and their approaches in learning which further indicate that positive perceptions lead to deep approaches in learning accounting, meanwhile negative perceptions lead to surface approaches of learning. When we test the relationship between learning approaches and students’ perceptions on the role of mobile apps in teaching and learning process, the result shows insignificant result which indicates that student could not perceive the role of mobile-apps technology in accounting subject. This is probably due to inexperience of using this tool in their learning experience as for time being mobile-apps has not been introduced as one of the teaching tools in accounting subject. Thus, this study implies that higher learning institutions in Malaysia still apply traditional method in accounting teaching and learning. Our study provides implications that accounting education in Malaysia need to consider the new reform in the teaching pedagogical method to accommodate the evolvement of technology in education process in this new era which may help to instill positive perception towards accounting subject.